TEACHERS’ SELF-EFFICACY IN IMPLEMENTING A CULTURE OF TEACHING AND LEARNING INNOVATION (International Journal of Creative Future and Heritage (TENIAT), 2023)
Self-efficacy refers to an individual’s belief in their capability towards executing behaviours necessary for specific performance attainments. Meanwhile, leadership is the action of leading a group of people or workers to complete the objectives and missions stated by an organisation or institution. Alternatively, innovation is a novel method, idea, product, or practice perceived as the new norm by an individual or other units of adoption. The purpose of this research was to identify the level of self-efficacy among teachers in Vocational College of different gender and different graduation status towards the implementation of innovation in the teaching and learning process. Thus, the research method utilised comprised a survey via a quantitative approach, while the instrument employed was a questionnaire consisting of 16 items, including demographic items. Purposive sampling was incorporated and teachers from five Vocational Colleges were involved in the data collection processes accordingly. The findings were processed using SPSS software (Statistics Protocol for Social Sciences). Results of the analytical calculations were expressed in terms of frequencies, percentages, mean values, standard deviation, and correlation. As such, Vocational College teachers were found to possess a high self-efficacy level (M = 4.10, s.d = 0.48) towards innovation implementation in the teaching and learning process. Henceforth, the results of this study can provide useful information to teachers for encouraging extensive efforts towards the implementation of innovation in the teaching and learning process. Efikasi kendiri merujuk kepada kepercayaan individu terhadap keupayaan mereka ke arah melaksanakan tingkah laku yang diperlukan untuk mencapai prestasi tertentu. Kepimpinan adalah tindakan mengetuai sekumpulan orang atau pekerja untuk menyelesaikan objektif dan misi yang dinyatakan oleh sesebuah organisasi atau institusi. Sebagai alternatif, inovasi adalah kaedah, idea, produk atau amalan yang dianggap sebagai norma baru oleh individu atau unit pengguna yang lain. Tujuan kajian ini adalah mengenal pasti tahap efikasi kendiri guru-guru di Kolej Vokasional yang berbeza jantina dan status tahap pendidikan ke arah pelaksanaan inovasi dalam proses pengajaran dan pembelajaran. Oleh itu, kaedah penyelidikan yang digunakan adalah pendekatan kuantitatif, manakala instrumen yang digunakan adalah soal selidik yang terdiri daripada 16 item, termasuk item demografi. Persampelan bertujuan melibatkan lima buah Kolej Vokasional. Hasil analisis dinyatakan dari segi frekuensi, peratusan, nilai min, sisihan piawai, dan korelasi. Analisis menunjukkan dapatan efikasi kendiri guru berada pada tahap yang tinggi (M = 4.10, s.d = 0.48) ke arah pelaksanaan inovasi dalam proses pengajaran dan pembelajaran. Justeru, hasil kajian ini dapat memberikan maklumat yang berguna kepada guru-guru untuk menggalakkan usaha yang meluas ke arah pelaksanaan inovasi dalam proses pengajaran dan pembelajaran.
Keywords: Culture of Teaching and Learning; Self-efficacy; Teaching and Learning Innovation; Budaya Pengajaran dan Pembelajaran; Efikasi Kendiri; Inovasi Pengajaran dan Pembelajaran